Child protection workers' understanding of the meaning and value of self-reflection in Estonia. Issue 2 (4th March 2019) - Toros, Karmen; LaSala, Michael C.
ABSTRACT: This article describes an exploratory qualitative study in Estonia that focuses on how child protection workers ( N = 93) perceive and understand the meaning and value of self-reflection. Participants discussed self-reflection in the context of self-analysis, motivation to improve professional performance, negative self-appraisal, and feedback from peers and clients. The findings highlight the workers' emphasis on self-perceived weaknesses, reflecting Estonian cultural norms which eschew self-praise and focus on deficits rather than strengths and possibilities. Self-reflection was mainly associated with a cognitive process, namely learning from the experience. This study underscores the need to guide and encourage child protection workers to adopt and apply systematic and possibly less critical self-reflection so that they can strengthen their decision-making process to promote the well-being of children and their families in the child welfare system.